The Reliability and validity of the Persian Version of Three-Factor Eating Questionnaire-R18 (TFEQ-R18) in Overweight and Obese Females - Seyed-Ali Mostafavi; Shahin Akhondzadeh; Mohammad Reza Mohammadi; Mohammad Reza Eshraghian; Saeed Hosseini; Maryam Chamari; Seyed Ali Keshavarz (Iranian Journal of Psychiatry, 2017)
Objective: The Three-Factor Eating Questionnaire Reduced (TFEQ-R18) is one of the most widely used instruments for assessing eating behavior worldwide. The present study aimed at confirming the reliability and validity of the Persian version of TFEQ-R18 among overweight and obese females in Iran.